Body-Weight Gain in Women During Smoking Cessation Is a Sex-Specific Predictor of 6-Month Abstinence: A Retrospective Cohort Study - Kuo, Chin-Wei; Lin, Chung-Fu; Chen, Chuan-Yu; Wang, Ru-Hsueh; Chou, Chieh-Ying; Cheng, Hsiang-Ju; Wu, Jin-Shang; Chen, Chang-Wen; Shieh, Chi-Chang; Yu, Tsung (Frontiers in Public Health, 2022)
Background: Smoking behavior differs between the sexes. Weight control is one of the main reasons leading to tobacco abuse in females but not in males. Studies on the predictive factors of cessation failure between sexes are scarce. This study is aimed to investigate the predictors of smoking cessation success, particularly weight change, for participants in smoking cessation program with different sexes. Methods: Participants of smoking-cessation program at a medical center in Taiwan between 2018 and 2019 were included. Details of age, sex, comorbidities, depression screening, nicotine dependence, body weight, and cessation medications of the participants were collected. The participants were classified based on their sex, and multivariable logistic regression analyses were conducted. For sensitivity analysis, multivariable logistic regression analyses were performed after stratifying the participants according to their weight loss (weight loss ≥1.5 kg and weight loss ≥3.0 kg). Results: A total of 1,475 participants were included. Body-weight gain in females was associated with failed abstinence (adjusted odds ratio (OR): 3.10, 95% confidence interval (CI): 1.10–9.04). In contrast, body-weight gain in males was associated with successful 6-month prolonged abstinence (adjusted OR: 0.77, 95% CI: 0.61–0.98). The adjusted ORs for any body-weight loss, body-weight loss ≥1.5 kg, and body-weight loss ≥3.0 kg were 0.28 (95% CI: 0.09–0.88), 0.14 (95% CI: 0.03–0.55), and 0.03 (95% CI: 0.01–0.42), respectively. Conclusion: Body-weight gain in females during a hospital-based smoking-cessation program is associated with abstinence failure. Further multicenter studies, including participants of different races and cultural backgrounds, are warranted.